Economic Integration, Sovereignty and Identity: New Zealand in the Global Economy - Megan Claridge; Sarah Box (New Zealand Government, The Treasury, 2000)
Markets are becoming more integrated. Whilst governments have limited influence over this process, they can hasten or hinder the pace of integration and will need to respond to the implications of integration. This paper provides a framework for thinking about the benefits and costs of market integration. It analyses how cross border flows of goods, services, capital and labour affect the living standards of New Zealanders in terms of both productivity and incomes as well as other, broader, aspects of living standards. Particular attention is paid to the areas of spatial economic analysis and national sovereignty and identity. Governments must consider a number of factors when thinking about their stance on integration. Further economic integration promises economic benefits for New Zealanders in terms of greater productivity and higher incomes. One risk, however, is that with increasingly free factor flows, government pursuit of integration may increase the risk of activity relocating offshore. The evidence on the overall effect of integration on income distribution is unclear, however we do know that there will be winners and losers. Decision-making power and feelings of identity seem to be important components of well-being - integration brings with it both risks and opportunities in these areas, as pressure is put on traditional forms of governance and identity, and new forms develop. Deciding how the costs and benefits of integration stack up ultimately involves a number of value judgements - the paper provides a framework and a summary of empirical evidence to help inform those judgements.
Keywords: 330